2015
DOI: 10.1016/j.ijwd.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrated papules on the trunk and headaches: A case of actinic granuloma and a review of the literature

Abstract: Actinic granuloma is a rare granulomatous reaction that is more commonly seen in females and thought to occur as an autoimmune response to actinic damage of elastic tissue. We discuss a case of a patient with actinic granuloma presenting with concomitant temporal arteritis. Our case and review of the literature emphasize the association between actinic granuloma and temporal arteritis, a serious inflammatory condition that could lead to blindness if misdiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Historically, actinic damage of the elastic tissue was recognised as the main cause 1 2. Recent reports, including ours, have described a paradoxical predominant affection of non-photoexposed skin and an absence of significant photoaging 2–4. Thus, the central role of ultraviolet radiation in the pathogenesis of EGCG has been questioned.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Historically, actinic damage of the elastic tissue was recognised as the main cause 1 2. Recent reports, including ours, have described a paradoxical predominant affection of non-photoexposed skin and an absence of significant photoaging 2–4. Thus, the central role of ultraviolet radiation in the pathogenesis of EGCG has been questioned.…”
Section: Discussionmentioning
confidence: 86%
“…We believe this cytokine profile of adipose tissue may have favoured a granulomatous type reaction against the nearby glycated elastic fibres. Nevertheless, other related disorders have been reported, specifically sarcoidosis, temporal arteritis, erythropoietic protoporphyria, and haematological and solid malignancies 1 3 8–11. Therefore, atypical cases of EGCG, particularly those non-photodistributed, demand the assessment of other comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of AG is challenging and no therapies have been evaluated in placebo‐controlled trials. Case reports and observational studies have reported treatment with topical and intralesional corticosteroids, psoralen ultraviolet A therapy, antimalarials, cyclosporine, methotrexate, systemic retinoids, cryotherapy (Parikh et al, ). While antimalarials are typically effective in the treatment of photodistributed disorders, AG and AEGCG have variable responses to these agents (Parikh et al, ).…”
mentioning
confidence: 99%
“…Our patient previously failed to respond to months of class I topi- Treatment of AG is challenging and no therapies have been evaluated in placebo-controlled trials. Case reports and observational studies have reported treatment with topical and intralesional corticosteroids, psoralen ultraviolet A therapy, antimalarials, cyclosporine, methotrexate, systemic retinoids, cryotherapy (Parikh et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation